Clinical outcome measures for progressive MS trials. (October 2017) - Ontaneda, Daniel; Cohen, Jeffrey A; Amato, Maria Pia
Treatment options for progressive multiple sclerosis remain the main unmet need of the field. As the understanding of multiple sclerosis (MS) pathogenesis improves, new pathways and molecules will be tested for potential reparative, remyelinating, or neuroprotective effects. The clinical outcomes used will determine successful demonstration of beneficial treatment effects to regulatory agencies, clinicians, and persons with MS. This review focuses on clinical outcome measures including the Expanded Disability Status Scale, Multiple Sclerosis Functional Composite, and novel composite measures of disability. The paper also covers cognitive outcomes and screening tests for use in clinical trials. The growing importance of patient-reported outcomes and their suitability for clinical trials is also presented. The review aims to create consensus in regard to these topics and suggestions for future research.